Vygotsky’s Zone Of Proximal Development and The Students’ Progress in Learning (A Heutagogcal Bibliographical Review) - Lasmawan, I Wayan; Budiarta, I Wayan (JPI (Jurnal Pendidikan Indonesia), 2020)
Inspired by the belief that Man’s power to change himself, that is, to learn, is perhaps the most impressive thing about him, the present study employs a library research with annotated bibliography to highlight the heutatgogical philosophy behind Vygotsky’s concept of Zone of Proximal Development. It is argued that the students’ learning progress results from the students’ personal experience, in which the students learn actively, establishing the students as the agents of learning. With this concept, it is believed that the students’ independent learning process can deliver them to the next level of their respective zone of potential development, from which process the zone of potential development will become the students’ zone of actual development, through which the students will enter their next zone of potential development, and so forth. This Heutatogical thinking is founded on the basic premise that (1) learning is centered and determined by the students, (2)  the students’ capability in applying relevant skills in familiar and unfamiliar conditions, (3) the students’ reflective and metacognitive process, (4) multiple repetitions, and (5) non-linear learning. Learning process in Vygotsky’s concept Zone of Proximal Development can be applied in Heutatogical thinking through (1) the settlement of learning contract, (2) improving the learning activities, and (3) learning assessment with heutatogical deisgns, namely exploration, creation, collaboration, connection, sharing, and reflection. However, it is important to highlight in the implementation of this Vygotskian Heutogogical learning is that the students’ backgrounds and characteristics should be closely observed, with a close monitoring of the possible conflicts occurring during the learning process as they develop their sense of responsibility as they conduct their independent learning collaboratively, which might be novel for students accustomed with conventional learning.